Dimensões da solidariedade intergeracional nas interações cotidianas de mães e avós de crianças com paralisia cerebral - Tiburcio, Izabella Mariana Gomes (Universidade Federal de São Carlos, 2020)
Introduction: Children with cerebral palsy who have epileptic syndromes may experience delays in neuropsychomotor, cognitive and social development. The greater the degree of involvement, the greater the need to support families that live with instability and stress in their daily lives. Objective: To describe dimensions of intergenerational family solidarity (SFI) in the daily interactions of mothers and grandparents of children with cerebral palsy who have epileptic syndromes. Method: Descriptive study with a qualitative and quantitative approach. Three mothers and three grandparents of children diagnosed with cerebral palsy and epileptic syndromes participated in the research. The instruments used were: Inventory Pedicat, Economic Classification Brazil and a set of scales to measure certain dimensions of Intergenerational Solidarity (functional, affective and conflictual), quality of life and relationships. Results: The data, described in the form of three case studies, reveal the presence of the dimensions of the SIF analyzed with similarities and differences depending on the characteristics of the actors, the conditions present in the contexts and the challenges that families face in their daily lives. In two cases studied, the presence of the functional dimension, proximity, communication and understanding was verified. On the other hand, one of the dyads revealed a lack of help and reciprocity, the presence of conflicts, negative feelings and isolation. Conclusion: The mother-grandmother dyads of children with cerebral palsy and epilepsy who have a high degree of dependence on routine activities benefit when the affective, functional dimensions are present with low levels of conflicts.
Dimensions of intergerational solidarity in everyday interactions of mothers and grandparents of children with cerebral paralysis
Keywords: Paralisia cerebral; Mães; Avós; Apoio; Solidariedade intergeracional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL